Alveococcosis of the liver – strategy of surgical treatment with special focus on liver transplantation. Issue 5 (16th September 2016) - Patkowski, W.; Kotulski, M.; Remiszewski, P.; Grąt, M.; Zieniewicz, K.; Kobryń, K.; Najnigier, B.; Ziarkiewicz‐Wróblewska, B.; Krawczyk, M.
Abstract: Background: Echinococcosis is a zoonosis caused by infestation with any of 4 (of the 16) members of the Echinococcus genus, namely Echinococcus granulosus, Echinococcus multilocularis, Echinococcus oligarthus, and Echinococcus vogelii . The aim of this retrospective analysis was to present the outcomes of patients undergoing liver resection and liver transplantation (LT) for E. multilocularis infection. Methods: A total of 44 patients who underwent surgical treatment of E. multilocularis infection in the period between 1989 and 2014 were included in the study cohort and retrospectively analyzed. Results: LT was performed in 22 patients (50.0%), including 4 of 26 patients undergoing initial non‐transplant management. Non‐transplant procedures comprised liver resection in 23 patients (88.5%), diagnostic laparoscopy in 2 (7.7%), and left adrenalectomy in 1 patient (3.8%). Post‐transplantation survival rates were 90%, 85%, and 75% at 1, 5, and 10 years, respectively. Conclusion: In conclusion, LT for E. multilocularis infection is a safe and effective treatment method.